Terapi Relaksasi Progresif Untuk Menurunkan Kecemasan Siswi Dalam Menghadapi Menarche - Jumrotin, Jumrotin; Suroso, Suroso; Meiyuntariningsih, Tatik (Faculty of Psychology Universitas 17 Agustus 1945 Surabaya, 2018)
Abstract The purpose of this study to determine the effectiveness of progressive relaxation therapy in reducing the anxiety students facing menarche. This research includes Quasi Experimental research with One Group Pretest and Posttest Design. Variables in this research is Progressive Relaxation as independent variable (X) and Anxiety face menarche as dependent variable (Y). The population in this study were students of grade V and VI MI Bahrul Ulum who have not experienced menarche (menstruation for the first time) a number of 45 students. Research subjects as many as 15 students were taken using purposive sampling technique with criteria: 1) subjects have not experienced menarche; 2) experience anxiety. Data were collected using an anxiety scale that scored with Likert scale. Research data were analyzed using t-test with the help of SPSS for Windows program. The results showed a significant decrease in anxiety in subjects facing menarche (p = 0.000 <0.05) between post-treatment progressive relaxation.Keywords: progressive relaxation, anxiety facing menarche, young women